Enhancing Students’ Writing Skills through English Movies-Watching Reports; an Improvement of Linguistic Competences: Writing Skills, English Movies - Muhammad Asrul Hasby; Sugianto Sugianto (Journal of Language and Literature Studies, 2021)
English movies by some EFL teachers and lecturers are designed for teaching writing classes because learners can see how any of words is pronounced by actors who are English native speakers and they are asked to write reports in line with the contents of movies. Besides, learners can make notes of new vocabulary taken from the movies. Therefore, this study is aimed at finding out the use of Englis Movies-watching reports in improving students’ writing skills at the Mandalika University of Education. The research was conducted by involving the students at the English Zone Club organization. The researcher plans to have the students in this english organization because they tend to be more focus on english writing than other English organization at UNDIKMA. The research design of the present study is a classroom action research design where the researcher apply English movies to treat writing classes. They are asked to watch and pay attention to certain English movies and demand them to write a report on what they would have just watched. The research data are collected by distributing writing test to measure any improvement made through watching English movies on students’ writing skills. To gain the students’ writing improvement of writing skills, researchers make notes around some cycles of applying English movies in the class. The result of data collection was then analyzed by using quantitative statistical analysis. The conclusion of this study showed that the use of English movies was effective to improve grammatical competence, vocabulary, sentence patterns, various language usages, and motivation to practice writing.